The Green Flag - Doyle, Arthur Conan (Saga Egmont, 2022)
‘The Green Flag’ is a collection of short stories from the much-loved ‘Sherlock Holmes’ author Sir Arthur Conan Doyle. First published in 1895, stories in the collection include archaeology thriller ‘The New Catacomb’, pirate tale ‘Captain Sharkey’ and the suspenseful ‘The Lord of Chateau Noir’. An enjoyable collection from the prolific author.